Differentiate y = (x^2 + 1)^1/3

Use the chain rule to do this. First set u= x^2 + 1. We chose u to be this because u1/3 is much simpler to differentiate. Then find du/dx = 2x. Now find dy/du = 1/3 * u-2/3 = 1/3 * (x2 +1)-2/3. Now by the chain rule, dy/dx = dy/du * du/dx. Therefore dy/ dx = 2x * (1/3 * (x2 +1)-2/3 )= 2x/3 * (x2+1)-2/3

Answered by Will W. Maths tutor

2908 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Use logarithms to solve the equation 3^(2x+1) = 4^100


Some videos I've made


A-level circle question


Given that log_{x} (7y+1) - log_{x} (2y) =1 x>4, 0<y<1 , express y in terms of x.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences